Good governance and foreign direct investment in Sri Lanka - Vinujah, V.; Sooriykumar, K.; Sireeranhan, A. (University of Jaffna, 2017)
Globalisation has led to an increase in foreign direct investment (FDI), which is most useful way to gain foreign investment. Hence, FDI has been used by developing countries as a tool to solve their economic problems in the recent past. It is important to ensure investment climate to attract FDI. There are many conditions to attract FDI. Good governance plays a more significant role in influencing FDI. Most of the times investors are ready to pay more for companies to have good governance standards. This research aimed at tracing the impact of good governance on FDI using the time series annual data from 2002 - 2015 in Sri Lanka. Data for FDI and governance indicators were collected from World Bank databank. The six world bank indicators on good governance are control of corruption (CC), government effectiveness (GE), regulatory quality (RQ), political stability and absence of violence (PV), rule of law (RL) and voice and accountability (VA). Augmented Dicky Fuller Test (ADF) was used to test whether these data are stationary or non-stationary. After checking the stationary of time series data, Cointegration regression model for foreign direct investment net flow was developed using fully modified Ordinary Least Square (OLS) method. This study concluded that there is a long run relationship among the good governance indicators and foreign direct investment. In order to increase the foreign direct investment, Sri Lankan Government should improve the good governance, especially, control of corruption and government effectiveness. The positive coefficient of dummy variable for GSP plus suggests that government should try to get back GSP plus to expand the export amount and destination for textile product. This export opportunity may attract foreign direct investment in Sri Lanka.
Keywords: Foreign direct investment; Good governance; Governance indicators; GSP plus; OLS method